Speculating on Jim Crow Queerness in African American Lesbian and Gay Life Writing. (25th April 2019) - Lewis, Christopher S
Abstract: The late twentieth-century life writing of Audre Lorde and Samuel Delany imagines black lesbian and gay experiences during the era of Jim Crow segregation and, in doing so, models a queer and speculative engagement with the tradition of African American life writing. By undermining the presumption that gender and sexual normativity worked as shields against racism during the Jim Crow era, Lorde and Delany, in Zami: A New Spelling of My Name: A Biomythography (1982) and The Motion of Light in Water: Sex and Science Fiction Writing in the East Village, 1957-1965 (1988), respectively, challenge conventions of sexual silence and gender propriety that have often made black lives legible in African American life writing. Furthermore, Lorde and Delany narrate their experiences with the physical and psychic pain of racism and with lesbian and gay sexual pleasure simultaneously; in doing so, they suggest that the history and presence of racism need not foreclose public black queer expression. By working against historic patterns of African American life writing, which has often used positivist claims about black reality to create narrators who are positioned as normative racial representatives, the speculative life writing of Lorde and Delany broadens our understanding of what was or could have been possible in terms of gender and sexuality for African Americans during the Jim Crow era and beyond.